2011
DOI: 10.1016/j.jpsychires.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Mean diffusivity and fractional anisotropy as indicators of disease and genetic liability to schizophrenia

Abstract: The goals of this study were to first determine whether the fractional anisotropy (FA) and mean diffusivity (MD) of major white matter pathways associate with schizophrenia, and secondly to characterize the extent to which differences in these metrics might reflect a genetic predisposition to schizophrenia. Differences in FA and MD were identified using a comprehensive atlas-based tract mapping approach using diffusion tensor imaging and high resolution structural data from 35 patients, 28 unaffected first-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
103
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 77 publications
(98 reference statements)
4
103
0
Order By: Relevance
“…6 Both a neurodevelopmental model, 7,8 implying that WM alterations are present before disease onset and a postonset progression model, indicating that structural brain abnormalities progress over time after disease onset, have been proposed. 9,10 In support of the neurodevelopmental model, several cross-sectional DTI studies have revealed microstructural WM alterations in frontotemporal and -parietal connections in first-degree relatives without symptoms, 11,12 in clinical high-risk populations before onset, 13,14 and in patients with early onset psychosis. 15 Indeed, the lifetime trajectory of WM alterations in schizophrenia suggests higher percentages of WM loss in the first years of the illness, implicating altered neurodevelopment.…”
Section: Introductionmentioning
confidence: 91%
“…6 Both a neurodevelopmental model, 7,8 implying that WM alterations are present before disease onset and a postonset progression model, indicating that structural brain abnormalities progress over time after disease onset, have been proposed. 9,10 In support of the neurodevelopmental model, several cross-sectional DTI studies have revealed microstructural WM alterations in frontotemporal and -parietal connections in first-degree relatives without symptoms, 11,12 in clinical high-risk populations before onset, 13,14 and in patients with early onset psychosis. 15 Indeed, the lifetime trajectory of WM alterations in schizophrenia suggests higher percentages of WM loss in the first years of the illness, implicating altered neurodevelopment.…”
Section: Introductionmentioning
confidence: 91%
“…Evidence from functional magnetic resonance imaging has shown that modulation of fronto-parietal connectivity during working memory processing was gradually reduced from healthy controls to ARMS subjects and then to first-episode patients (FEP) [14], suggesting that fronto-parietal connectivity changes in psychosis evolve along a dynamic trajectory, emerging before disease onset and developing with ongoing illness. DTI studies have shown reduced FA in the SLF in patients with FEP [15], as well as in subjects at clinical [16,17] or genetic high-risk of psychosis [18,19] (for a review see [11]). DTI studies have also observed increased MD in the SLF of genetic [18] and clinical high-risk individuals [17].…”
Section: Introductionmentioning
confidence: 99%
“…DTI studies have shown reduced FA in the SLF in patients with FEP [15], as well as in subjects at clinical [16,17] or genetic high-risk of psychosis [18,19] (for a review see [11]). DTI studies have also observed increased MD in the SLF of genetic [18] and clinical high-risk individuals [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, COS is a rare and more severe form of AOS and has a more pronounced genetic risk (Asarnow and Asarnow, 1994;Asarnow and Forsyth, 2013;Asarnow et al, 2001;Nicolson and Rapoport, 1999). There have been extremely few DTI studies in this population; Moran et al (2015) and Clark et al (2011) found decreased FA in COS patients, and Ashtari et al (2007) found decreased FA in early onset schizophrenia (defined as onset before the age of 18) patients.…”
Section: Introductionmentioning
confidence: 99%